Stem Cell Therapy for Myocardial Infarction: A Mini-Review - Hussain, Md Sadique; Tyagi, Swati; Khatri, Himanshi; Singh, Sandeep (Asian Journal of Pharmaceutical Research and Development, 2022)
Stem cells are undifferentiated cells that can proliferate, regenerate, develop into differentiated cells, and produce a variety of tissues. Embryonic stem cells, adult or somatic stem cells, and pluripotent stem cells are the three types of stem cells. Another classification of stem cells is totipotent, multipotent, and unipotent cells. Stem cell treatment has the possibility of treating degenerative disorders, cancer, and the restoration of damaged tissues, all of which now have no or restricted medicinal alternatives. Myocardial infarction is a potentially fatal condition caused by the permanent loss of cardiomyocytes and a deterioration in the heart’s blood-pumping capacity. Throughout the last two decades, stem cell-based treatments for myocardial infarction therapy have been researched with encouraging results. Traditional therapy for myocardial infarction slows disease development but has little effect on healing. Because of their ability to initiate de novo cardiogenesis, embryonic stem cells are thought to be a potential candidate for cardiac regeneration.